Curve Sprinting in Soccer: Kinematic and Neuromuscular Analysis - Filter, A.; Olivares-Jabalera, J.; Santalla, A.; Morente-Sánchez, J.; Robles-Rodriguez, J.; Requena, B.; Loturco, I. (International Journal of Sports Medicine, 2020)
Sprinting in curvilinear trajectories is an important soccer ability, corresponding to ~85% of the actions performed at maximum velocity in a soccer league. We compared the neuromuscular behavior and foot contact-time between outside leg and inside leg during curve sprinting to both sides in soccer players. Nine soccer players (age=23±4.12 years) performed: 3×Sprint linear, 3×Sprint right curve, and 3×Sprint left curve. An ANOVA with repeated measures was used to compare the differences between inside and outside leg, and Cohen`s d was used to calculate the effect-size. Considering the average data, the performance classification (from best to worst) was as follows: 1. Curve "good" side (2.45±0.11 s), 2. Linear (2.47±0.13 s), and 3. Curve "weak" side (2.56±0.17 s). Comparing linear with curve sprinting, inside leg recorded significant differences ("good" and "weak"; effect size=1.20 and 2, respectively); in contrast, for outside leg, there were no significant differences ("good" and "weak"; effect size=0.30 and 0.49, respectively). Electromyography activity showed significant differences (p=0.05) during curve sprinting between outside (higher in biceps femoris and gluteus medius) and inside leg (higher activity in semitendinosus and adductor). In summary, inside and outside leg play different roles during curved sprints, but inside leg is more affected by the change from straight to curve sprint.